Association between scapulo-vertebral distance and shoulder pain in athletes from a private university in Lima: preliminary study - Ospinal Muedas, Evelyn Susan (2021)
Introduction: Shoulder pain cases represents about 7% to 50% in the population and its prevalence in athletes between 15 and 19 years old is about 43.5%. Additionally, another pathology in the upper limb is scapular dyskinesia, caused by the scapular´s movements and position alteration. Objective: To determine association between scapula-vertebral distance and shoulder pain in athletes from a private university in Lima. Materials and Methods: Cross-sectional analytical study - preliminary. The study population were athletes from a private university in Lima. The shoulder pain variables were measured by four orthopedic tests Jobe, Patte, Gerber, and Hawkins Kennedy, where shoulder pain (YES) is considered when at least one of the tests is positive and no shoulder pain (NO) when all tests are negative. And the scapular-vertebral distance variables were evaluated in three positions, by the lateral scapular sliding test (LSST); measured in (cm). Results: 51 athletes from climbing, rugby, volleyball, and basketball sports were evaluated in this study. The age ranged was 19 to 21 years. The scapula-vertebral distance of the right side was mayor than the left. 17.65% had shoulder pain. The frequency of training and sex associated with shoulder pain (p<0.05). The scapula-vertebral distance from athletes who had shoulder pain was higher than those without it (p<0.05). Conclusion: Was found association between scapula-vertebral and shoulder pain in athletes from a private university in Lima. Its recommended doing more researches with a considerable sample to reach an adequate statistical power.